Beetroot supplementation improves the physiological responses to incline walking - Mark Waldron (European Journal of Applied Physiology, 2018)
PURPOSE:We investigated the effects of an acute 24-h nitrate-rich beetroot juice supplement (BR) on the energy cost, exercise efficiency and blood pressure responses to intermittent walking at different gradients.METHODS:In a double-blind, cross-over design, eight participants were provided with a total of 350 ml of nitrate-rich (~ 20.5 mmol nitrate) BR or placebo (PLA) across 24 h before completing intermittent walking at 3 km/h on treadmill at gradients of 1, 5, 10, 15 and 20%.RESULTS:Resting mean arterial pressure (MAP) was ~ 4.1% lower after BR (93 vs. 89 mmHg; P = 0.001), as well as during exercise (102 vs. 99 mmHg; P = 0.011) and recovery (97 vs. 94 mmHg; P = 0.001). Exercising (1227 vs. 1129 ml/min P < 0.001) and end-stage (1404 vs. 1249 ml/min; P = 0.002) oxygen uptake ([Formula: see text]O2) was lower in BR compared to PLA, which was accompanied by an average reduction in phase II [Formula: see text]O2 amplitude (1067 vs. 940 ml/min; P = 0.025). Similarly, recovery [Formula: see text]O2 (509 vs. 458 ml/min; P = 0.001) was lower in BR. Whole blood potassium concentration increased from pre-post exercise in PLA (4.1 ± 0.3 vs. 4.5 ± 0.3 mmol/L; P = 0.013) but not BR (4.1 ± 0.31 vs. 4.3 ± 0.2 mmol/L; P = 0.188).CONCLUSIONS:Energy cost of exercise, recovery of [Formula: see text]O2, MAP and blood markers were ameliorated after BR. Previously-reported mechanisms explain these findings, which are more noticeable during less-efficient walking at steep gradients (15-20%). These findings have practical implications for hill-walkers.